Hubungan Pemahaman Wajib Pajak dengan Kualitas Pelayanan Pajak Berbasis Coretax - Salam, Iqbal Alfitra; Rahayu, Puji (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2026)
The modernization of tax administration through the implementation of the Coretax system is a strategic step to improve the efficiency, transparency, and accountability of tax services in Indonesia. However, the success of this digital system is not only determined by technological readiness, but also by taxpayers' level of understanding of tax regulations and their ability to utilize technology-based services. Therefore, this study aims to analyze the relationship between taxpayer understanding and the quality of Coretax-based tax services and its implications for taxpayer compliance behavior.This study uses a quantitative approach with a survey method of taxpayers who have utilized Coretax digital services in the KPP Pratama environment. The sampling technique was non-probability. Primary data was collected through structured questionnaires and analyzed using linear regression or SEM-PLS to test the relationship between variables. Taxpayers' understanding was measured based on their knowledge of regulations, procedures, and electronic tax payment mechanisms. Meanwhile, the quality of Coretax-based services included ease of use of the system, reliability of services, responsiveness of officers, and clarity of information provided to taxpayers.Previous studies have shown that tax understanding and tax service quality have a positive effect on taxpayer compliance. However, in the digital context, limitations in literacy and technical constraints of the system have the potential to reduce taxpayers' perception of service quality and trust. This study is expected to provide evidence for Coretax service strategies.